2023
DOI: 10.1007/s00415-023-11912-x
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system complications in SARS-CoV-2-infected patients

Abstract: Objective To investigate the clinical manifestations, treatment and prognosis of COVID-19-associated central nervous system (CNS) complications. Methods In this single-centre observation study, we recruited patients with COVID-19-associated CNS complications at the neurology inpatient department of the Eighth Affiliated Hospital, Sun Yat-Sen University (Futian, Shenzhen) from Dec 2022 to Feb 2023. Patients were analysed for demographics, clinical manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Also, neurological symptoms, such as headaches and smell or taste disorders, were observed significantly more often in COVID-19 patients compared to Influenza -infected patients. Several studies have proposed/shown that SARS-CoV-2 also affects the nervous system [ 31 , 35 , 36 ] and might affect brain function by inducing neuroinflammatory cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Also, neurological symptoms, such as headaches and smell or taste disorders, were observed significantly more often in COVID-19 patients compared to Influenza -infected patients. Several studies have proposed/shown that SARS-CoV-2 also affects the nervous system [ 31 , 35 , 36 ] and might affect brain function by inducing neuroinflammatory cascades.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 may enter brain by crossing neural-mucosal interface in olfactory mucosa or via the gustatory-olfactory trigeminal pathway ( Jiao et al., 2021 ; Meinhardt et al., 2021 ; Beckman et al., 2022 ; Frank et al., 2022 ). The induction of excessive neuroinflammation has been reported to be a critical pathogenetic factor ( Frank et al., 2022 ; Chaves-Filho et al., 2023 ; Ousseiran et al., 2023 ; Theoharides and Kempuraj, 2023 ; Li et al., 2023a , Li et al., 2023b ). The neurovascular inflammation leads to the damage of blood–brain barrier (BBB), and the neuron hypoxic-ischemic injury and neuron degeneration ( Bodnar et al., 2021 ; Lee et al., 2021 ; Meinhardt et al., 2021 ; Adesse et al., 2022 ; Beckman et al., 2022 ; Frank et al., 2022 ; Rutkai et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%